Deformacja i pozorność dialogu w kontekście quasi-relacji społecznych - Brzozowski, Tomasz Tadeusz (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2013)
This text covers a wide range of problems in social relationships. In the Author’s opinion, a present social reality doesn’t allow deeper contacts between people. Current understanding of the concept of the dialogue, reduces it to negotiations or communication acts. But none of them isn’t a suitable substitute of the dialogue with its richness of a sense. The present time is characterized by superficiality of relationships in societies. Instead of the dialogue, we deal with only quasirelationship. People haven’t lost ability of reflective and critical reception of their life and they can’t feel existence of others as someone important, unique and indispensable for a proper and authentic meeting. In the dialogue, everybody shapes a meeting as momentous event. Different understanding of the depth this concept, can lead up to reduction of relationships in modern society. Misinterpretation of the dialogue concept makes our life common, mediocre, trashy. The article analyzes a moral condition of modern society and points at possible and existing threats in a field range of people’s relationships.